Cell Fate Determining Molecular Switches and Signaling Pathway in Pax7-expressing Somitic Mesoderm - Cheuk Wang Fung; Zhu, Han; Zhou, Shaopu; Wu, Zhenguo; Wu, Angela R (bioRxiv, 2019)
Pax7-expressing progenitor cells in the somitic mesoderm differentiate into multiple lineages, such as brown adipose tissue, dorsal dermis, as well as muscle in the dorsal trunk and the diaphragm; however, the key molecular switches that determine and control the process of lineage commitment and cell fate are unknown. To probe the mechanisms behind mesoderm development, Pax7creER/R26-stop-EYFP embryos were tamoxifen-induced at E9.5 to label Pax7+ cells for lineage tracing and collected at later time points for analysis. The YFP-labelled cells which belonged to the Pax7 lineage were enriched by fluorescence-activated cell sorting (FACS) and subject to single-cell RNA profiling. We observed that a subpopulation of cells differentiated into the myogenic lineage, showing Myf5 expression as early as E12.5, whereas the rest of the population was fibroblast-like and appeared to be the early stage of the adipogenic and dermal lineages. Cells at E14.5 had distinct myogenic populations that expressed Myod1 and Myog; we also identified other populations with Ebf2 or Twist2 expression, which could belong to adipogenic or dermal lineages, respectively. Cell surface markers were also found for each specific lineage, providing insights in sorting strategy for lineage-of-interest for further functional evaluation. Adipogenic lineage was successfully sorted with a combination of Pdgfra and Thy1 antibodies. In addition, we found that upregulation of Wnt signaling pathway activity is dynamically regulated in dermal lineage. Finally, transcription factors that could potentially drive, or reprogram cell fate, were identified at different developmental time points.